Human enteric viruses in a wastewater treatment plant: evaluation of activated sludge combined with UV disinfection process reveals different removal performances for viruses with different features. (6th February 2018) - Lizasoain, A.; Tort, L.F.L.; García, M.; Gillman, L.; Alberti, A.; Leite, J.P.G.; Miagostovich, M.P.; Pou, S.A.; Cagiao, A.; Razsap, A.; Huertas, J.; Berois, M.; et al.
Abstract: This study assess the quality of wastewater through the detection and quantification of important viruses causing gastroenteritis at different stages of the wastewater treatment process in an activated‐sludge wastewater treatment plant with ultraviolet disinfection. Ten sampling events were carried out in a campaign along a period of 18 months collecting wastewater samples from the influent, after the activated‐sludge treatment, and after the final disinfection with UV radiation. Samples were concentrated through ultracentrifugation and analysed using retro‐transcription, PCR and real time quantitative PCR protocols, for detection and quantification of Group A Rotavirus (RVA), Human Astrovirus (HAstV), Norovirus Genogroup II (NoV GII) and Human Adenovirus (HAdV). HAdV (100%), NoV GII (90%), RVA (70%) and HAstV (60%) were detected in influent samples with concentration from 1·4 (NoV GII) to 8·0 (RVA) log10  gc l −1 . Activated‐sludge treatment reached well quality effluents with low organic material concentration, although nonstatistical significant differences were registered among influent and postactivated sludge treatment samples, regarding the presence and concentration for most viruses. All post‐UV samples were negative for NoV GII and HAstV, although RVA and HAdV were detected in 38% and 63% of those samples respectively, with concentration ranging from 2·2 to 5·5 and 3·1 to 3·4 log10  gc l −1 . Significance and Impact of the Study: This study demonstrates that an activated‐sludge wastewater treatment plant with UV disinfection reduces to levels below the detection limit those single‐stranded RNA viruses as noroviruses and astroviruses and reach significant lower levels of rotaviruses and adenoviruses after the complete treatment process. Abstract : Significance and Impact of the Study: This study demonstrates that an activated‐sludge wastewater treatment plant with UV disinfection reduces to levels below the detection limit those single‐stranded RNA viruses as noroviruses and astroviruses and reach significant lower levels of rotaviruses and adenoviruses after the complete treatment process.